Evidence that Two‐Year‐Old Children are Sensitive to Information Presented in Arguments. (26th July 2017) - Castelain, Thomas; Bernard, Stéphane; Mercier, Hugo
Abstract : Preschoolers are more likely to endorse testimony supported by strong arguments than by weak, circular ones. Two‐year‐olds exchange arguments with others, but no experiment has demonstrated that they are sensitive to information presented as argument. In the first phase of this study, 2‐year‐olds were shown ambiguous pictures—for instance a bird–fish hybrid—and asked what they thought the picture represented. An informant then contradicted them, providing either a strong argument, a circular argument, or no argument, and the children were asked what they now thought the hybrid was. The second phase was identical to the first, with new hybrids, except that the informant never provided any argument for her position. Finally, in the third phase, the informant left the room and the children were asked again to tell what the hybrids from the first two phases were. On the whole, there was an effect of the amount of information provided in the argument so that children were more likely to endorse labels provided by the informant who had supported her answer with a strong argument in the first phase. Moreover, they generalized the trust granted to informants who provided strong arguments. These results constitute the first experimental demonstration that 2‐year‐olds possess some argument evaluation skills.